Utility of the lateral arm free flap in oral cavity reconstruction: a single-centre experience with Chinese patients. Issue 10 (October 2020) - Jia, M.-Q.; Zou, H.-X.; Xiong, X.-P.; Ma, S.-R.; Yu, S.; Wei, L.-L.; Jia, J.
Abstract: The lateral arm flap (LAF) may offer an alternative option for oral cavity repair. Twenty-five Chinese patients with oral cavity defects were reconstructed with a LAF. The anatomical characteristics of the flap, the donor site complications, and the functional and aesthetic assessments of recipient site were reviewed. The overall flap survival was 96.0% (24/25patients). The average pedicle length was 7.07 ± 1.09 cm when it was cut off at the insert of the deltoid, with an average arterial diameter of 1.30 ± 0.37 mm and vein diameter of 2.06 ± 0.48 mm. The average flap length was 7.06 ± 1.01 cm, and the average flap breadth was 5.28 ± 0.66 cm, with the average flap size ranging from 18 to 42 cm 2 . One to three reliable perforators supplied the flap, with the proximal, middle, and distal perforators being located at 9.9 ± 1.1 cm, 8.6 ± 1.4 cm, and 5.7 ± 1.2 cm from the lateral epicondyle, respectively. The donor defect was closed primarily and healed uneventfully. A longitudinal scar was the most common morbidity of the donor site. The function and shape of the reconstructed tissues were well restored. The LAF provides a reliable choice for reconstructing medium-sized oral cavity defects, with minimal donor-site morbidity and ideally functional and aesthetic rehabilitation of the recipient site.